Engaging the Intellectual and the Moral in Critical Literacy Education: The Four-Year Journeys of Two Teachers From Teacher Education to Classroom Practice - Jones, Stephanie; Enriquez, Grace (Reading research quarterly, 2009)
As teachers are increasingly being asked and expected to teach across cultural differences and work toward social justice in their classrooms, teacher educators must seriously consider how university course work impacts students in their own classrooms. This article present a four-year qualitative case study investigating the meaning-making of two students in a graduate course focused on literacy and culture during the semester the course was taken and their subsequent entrance into the classroom to teach primary grade students. The authors use Bourdieu's constructs of habitus, field, and capital to better understand when, where, and why teachers take up critical literacy practices across time and context. The authors argue that teacher education pedagogy is merely a point of contact and a point of departure for learners and that nuanced, long-term readings of teacher education students' improvisations of habitus reveal the interplay between their formal learning and their personal, social, political, and other formal educational experiences. The impact of university course work can prompt small or significant changes in habitus and the interactions between habitus and particular fields (graduate course, life, elementary school, and literacy pedagogy) can both reinforce a critical literacy perspective and constrain that perspective.